Atrophy mainly affects the limbic system and the deep grey matter at the first stage of multiple sclerosis - Audoin, Bertrand; Zaaraoui, Wafaa; Reuter, Françoise; Rico, Audrey; Malikova, Irina; Confort-Gouny, Sylviane; Cozzone, Patrick J; Pelletier, Jean; Ranjeva, Jean-Philippe (Journal of neurology, neurosurgery and psychiatry, 2010)
BackgroundThe existence of grey matter (GM) atrophy right after the first clinical event suggestive of multiple sclerosis (MS) remains controversial. The aim of this study was therefore to establish whether regional GM atrophy is already present in the earliest stage of MS assessing regional GM atrophy in a large group of patients.MethodsSixty-two patients with a clinically isolated syndrome (CIS) were examined on a 1.5 T MR imager within 6 months after their first clinical events. A group of 37 matched healthy control subjects were also included in the study. An optimised voxel-based morphometry (VBM) method customised for MS was applied on volumetric T1-weighted images. The functional status of patients was assessed using the Expanded Disability Status Scale (EDSS) and the Brief Repeatable Battery.ResultsVBM analysis (p<0.005, familywise error corrected) on patients versus control subjects showed the presence of significant focal GM atrophy in patients involving the bilateral insula, the bilateral orbitofrontal cortices, the bilateral internal and inferior temporal regions, the posterior cingulate cortex, the bilateral thalami, the bilateral caudate nuclei, the bilateral lenticular nuclei and the bilateral cerebellum. EDSS was slightly correlated (ρ=−0.37 p=0.0027) with the atrophy of the right cerebellum. No correlations have been evidenced between the cognitive status of patients and the regional GM atrophy.ConclusionThe present study performed on a large group of CIS patients demonstrated that regional GM atrophy is present right after the first clinical event of multiple sclerosis and mainly affects the deep GM and the limbic system.